2014
DOI: 10.4049/jimmunol.1303420
|View full text |Cite|
|
Sign up to set email alerts
|

Staphylococcus aureus Infection of Mice Expands a Population of Memory γδ T Cells That Are Protective against Subsequent Infection

Abstract: The development of vaccines against S. aureus has consistently failed in clinical trials, likely due to inefficient induction of cellular immunity. T cell-derived IL-17 is one of the few known correlates of anti-staphyloccoal immunity, conferring protection against S. aureus infections through its ability to promote phagocytic cell effector functions. A comprehensive understanding of the discrete T cell subsets critical for site-specific IL-17-mediated bacterial clearance will therefore be necessary to inform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
115
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 62 publications
4
115
1
Order By: Relevance
“…In another study, peritoneal infection with Staphylococcus aureus led to the persistence of an expanded population of Vγ6 + γδT cells. Again the expanded cells showed restricted tissue tropism, persisting in the peritoneum and draining LNs (22). Our findings for Vγ4 + Vδ4 + cells provide further evidence for the ability of γδT cells to acquire memory characteristics including accelerated activation and proliferation after reencountering a stimulus.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In another study, peritoneal infection with Staphylococcus aureus led to the persistence of an expanded population of Vγ6 + γδT cells. Again the expanded cells showed restricted tissue tropism, persisting in the peritoneum and draining LNs (22). Our findings for Vγ4 + Vδ4 + cells provide further evidence for the ability of γδT cells to acquire memory characteristics including accelerated activation and proliferation after reencountering a stimulus.…”
Section: Discussionsupporting
confidence: 53%
“…Memory responses are a defining feature of the conventional αβT-cell compartment, yet whether γδT cells develop immune memory has been investigated less. Recent studies of Vγ6 + intestinal and peritoneal cells have begun to provide support for γδT-cell memory responses (21,22). However, it is not yet clear whether dermal γδT17 cells can take on memory characteristics.…”
mentioning
confidence: 99%
“…Collectively, our current data demonstrate a clear role for IL-10 in controlling T cell and phagocyte activation, which subsequently dictates disease outcome during two contrasting S. aureus infection types. Previously published data have now demonstrated that cellular responses, including Th1, Th17, and gd + T cell responses, are all involved in the host defense against S. aureus infections (30,32,34,40); however, their relative prominence varies depending on whether the infection is local or systemic, the anatomical site of the local infection, and whether the infection is acute or chronic. As the skin is the largest organ of the body and an important barrier against invading bacteria, it comprises a complex immune system involving DCs, keratinocytes, T cells, and regulatory B cells that create a tolerant microenvironment to prevent undesirable inflammation in response to commensal organisms (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we demonstrate that IL-10 acts upstream of effector T cells, controlling their cytokine responses. We have previously shown that gd-derived IL-17 and type I immune responses are required at different stages of S. aureus peritoneal infection to promote effective bacterial clearance through the ability of these cytokines to regulate downstream phagocyte responses (30,32). However, it appears that these T cell responses cannot be allowed to proceed unchecked and that effective resolution of infection requires the gd + T cell and CD4 + T cell responses to be tightly controlled so as to avoid host pathology that would ensue from excessive phagocyte activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation